Analysis of Students' Misconceptions in Solving Story Problems on Operations Material for Calculating Decimal Fractions for Class V Elementary School in View of Mathematical Ability - Sudarmiani Wahyu Sungkono; Feny Rita Fiantika; Susi Hermin Rusminati (Formosa Journal of Sustainable Research, 2023)
The study aims to characterize students' misconceptions regarding decimal fraction calculations based on their mathematical proficiency. This research is qualitative in nature. Fifth grade students at SDN Dukuh Menanggal I Surabaya were the research subjects, consisting of three students with high mathematics abilities, one student with moderate mathematics abilities, and one student with low mathematics abilities. Written tests and interviews were used as data collection methods, and misconception tests consisting of description questions and interview guides were used as research instruments. Research findings show that, contrary to popular belief, students who are highly skilled in mathematics make errors when writing numbers in their answers, even when the answers are unrelated to the question. When calculating the results of decimal fraction calculations, students with moderate abilities make mistakes due to misconceptions. Meanwhile, students with low ability have misconceptions when they do their work correctly, do not work seriously, and cannot understand the meaning of the questions